IMPLEMENTASI PENDEKATAN PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA PADA MATERI TEKANAN PADA SISWA KELAS VIII SMPN 1 MUARA UYA - Isna Farida (Universitas Lambung Mangkurat, 2012)
This Classroom Action Research aims to improve the activity and the learning outcomes of students of SMPN 1 Muara Uya, through guided inquiry approach. This research was conducted in two cycles to a class which consist of 27 learners. Collecting datas technique were conducted through observations by teachers and collaborators along the learning prosess and achievement test given in the end of learning. Data was analyzed qualitatively. Activity level learners expressed by categories high, medium, and low, while the learning outcomes expressed with mastery and inmastery. This research concluded that: 1). involvement of learners in the learning process as active 2). teacher activity is quite active with a mean score of 2.75 and 3.0 in the first cycle, whereas in the second cycle with a mean of 3.0 and 3.6 in good categories 3). student learning outcomes increased from 85.2% in the first cycle and 100% in the second cycle exceeds 75% of the criteria that have been established. So, implementation of inquiry approach can improve the activity and learning outcomes of students in learning science in the eighth grade students of SMPN 1 Muara Uya.Key words: guided inquiry approach, learning activities, learning outcomes